2009
DOI: 10.1515/znb-2009-1014
|View full text |Cite
|
Sign up to set email alerts
|

Three New Unsaturated Fatty Acids from the Marine Green Alga Ulva fasciata Delile

Abstract: From the dichloromethane extract of the marine green alga Ulva fasciata Delile, collected from the Mediterranean coast of Egypt, three new fatty acids, namely, (E)-11-oxo-octadeca-12-enoic acid (1a), (E)-11-hydroxy-octadeca-12-enoic acid (2a) and 6-hydroxy-oct-7-enoic acid (3a) together with cholesterol were isolated. Analysis of the unpolar part of the extract using GC-MS detected the existence of further ten compounds, namely, dimethylsulfoxide, dimethylsulfone, phenylacetamide, 6,10,14-trimethyl-pentadecan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
4
5
0
Order By: Relevance
“…S12, Supporting Information). Dereplication and further MS/MS fragmentation indicated that 3 is ( E )-11-oxooctadec-12-enoic acid (Figure 2), previously reported from the marine green alga Ulva fasciata [16] (Fig. S10, Supporting Information).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…S12, Supporting Information). Dereplication and further MS/MS fragmentation indicated that 3 is ( E )-11-oxooctadec-12-enoic acid (Figure 2), previously reported from the marine green alga Ulva fasciata [16] (Fig. S10, Supporting Information).…”
Section: Resultssupporting
confidence: 56%
“…is (E)-11-oxooctadec-12-enoic acid ( Figure 2), previously reported from the marine green alga Ulva fasciata [16] (Fig. S10, Supporting Information).…”
Section: (Fig S12 Supporting Information) Dereplication and Furthesupporting
confidence: 62%
“…321 Feeding experiments using 13 C-labelled sodium acetate precursors revealed that all 25 carbon atoms in the skeleton of aspergiolide A, a metabolite of the filamentous fungus Aspergillus glaucus, 322,323 were derived from labelled acetate. A bioactivity-directed analysis of Ulva fasciata (Aabu-Qir, Mediterranean coast, Egypt) characterised three new unsaturated fatty acids 293-295 and a further ten known nonpolar metabolites identified by GC-MS. 331 The ubiquitous monoterpene loliolide 332 was found in thirteen red, brown and green algae from the Black Sea. 325 Biosynthetic studies of curacin A, a metabolite of mixed polyketide-peptideorigin from the cyanobacterium Lyngbya majuscula, 326 revealed an unprecedented decarboxylative chain termination mechanism involving a module containing adjacent sulfotransferase (ST) and thioesterase (TE) catalytic domains.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…Fatty acids have been reported as bioactive metabolites to lower diabetes incidence [52] . In contrast, biological actions reported for hydroxylated fatty acids (oxylipids) included cytotoxic, anti-inflammatory and antimicrobial effects [53] , previously reported in luffa fruits and seeds [17] , [54] .…”
Section: Resultsmentioning
confidence: 98%